2020
DOI: 10.1007/s11033-020-05490-8
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequence analysis of Cupriavidus campinensis S14E4C, a heavy metal resistant bacterium

Abstract: Cupriavidus sp. are model organisms for heavy metal(loid) resistance and aromatic compound's degradation studies and these characteristics make them a perfect candidate for biotechnological purposes. Bacterial strain S14E4C (identified as Cupriavidus campinensis) was isolated from a playground by enrichment method in a 0.25 mM containing medium. The analysis revealed that this bacterium is able to tolerate high concentrations of heavy metal(loid)s: Cd up to 19.5 mM, Pb to 9 mM, Hg to 5.5 mM and As to 2 mM in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…gilardii [80], C. campinensis [81] and C. neocaledonicus [82] are considered to be metal resistant. Many of these genes confer resistance to metals by means of intracellular metal sequestration to facilitate export, as in the case of CopZ with Cu + ions [83], Ag + and Cd 2+ ions [84].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…gilardii [80], C. campinensis [81] and C. neocaledonicus [82] are considered to be metal resistant. Many of these genes confer resistance to metals by means of intracellular metal sequestration to facilitate export, as in the case of CopZ with Cu + ions [83], Ag + and Cd 2+ ions [84].…”
Section: Discussionmentioning
confidence: 99%
“…Together, the MRGs listed in Table 1 contribute to resistance to copper, silver, magnesium, cobalt, mercury, molybdenum, arsenic, zinc, cadmium, iron, antimony and nickel. Many species of Cupriavidus including C. pauculus [ 76, 77 ], C. metallidurans [ 78, 79 ], C. gilardii [ 80 ], C. campinensis [ 81 ] and C. neocaledonicus [ 82 ] are considered to be metal resistant. Many of these genes confer resistance to metals by means of intracellular metal sequestration to facilitate export, as in the case of CopZ with Cu + ions [ 83 ], Ag + and Cd 2+ ions [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other notable genes mined from our metadata include drrABC, daunorubicin resistance genes 37 ; phzEFH, phenazine biosynthesis protein (biocontrol); 38 fepBCDEG, siderophore enterobactin or ferric enterobactin transport ATP-binding protein; 39 czcC, heavy metal efflux protein to resist the effect of cobalt, zinc and cadmium 40 ; soxBXYZ, sulfur oxidizing multi-enzyme genes 41 ; trehalose synthase, uptake of exogenous trehalose 42 and cysteine desulfurase family (sufs, iscs and csdA). 43…”
Section: Discussionmentioning
confidence: 99%
“…HMR-1 isolated from waste water proves it to be having resistance towards multiple heavy metals especially cadmium 25 . Additionally, one more finding of Cupriavidus compinesis S14E4C exhibited its ability to tolerate cadmium upto 19.5mM 26 . Genomic screening of Bacillus cereus NWUAB01 revealed that it can tolerate 200 mg/L of Cd 27 .…”
Section: Biochemical and Molecular Characterizationmentioning
confidence: 96%